(untitled) (Academic Journal of Internal Affairs, 2023)
Aim: The first half of the two-part study presents the physical methods of latent print developments, method classification, brief history, and future trends. Methodology: The study synthesizes some of the most important technical handbooks and dozens of articles, published in the last decades. It also includes my own previously published research results. Findings: The so-called physical methods of latent print development are still under ongoing research. Methods from the 19th century, like powdering, are still being developed. VMD has once been replaced by cyanoacrylate fuming in the late seventies, but in the last 1-2 years it is spreading again. Value: In the Hungarian literature, such a comprehensive review has not been published on this subject for a long time.